Bacteriological and pathological investigations on the preputial glands of one-year-old C57BL/6NCrl mice maintained in individually ventilated cages. (June 2022) - Di Caro, Gianfranco; Minoli, Lucia; Ferrario, Marzia; Marsella, Gerardo; Milite, Gianpaolo; Crippa, Luca; Martino, Piera Anna; Paltrinieri, Saverio; Scanziani, Eugenio; Recordati, Camilla
Spontaneous infections of the preputial glands represent overlooked health problems in mice that could raise welfare concerns and potentially confound scientific experiments. Agents involved in preputial gland infections have rarely been investigated, with opportunistic pathogens of laboratory animals usually detected in inflamed preputial glands. The aim of this study was to investigate the prevalence of bacterial infection in the preputial glands and the relationship between haematological and pathological changes and infection status. We analysed 40 preputial glands from 20 one-year-old C57BL/6NCrl male mice by using bacteriology, haematology and pathology. Bacteria were isolated from 16/20 (80%) mice, for a total of 32/40 (80%) examined preputial glands. Enterobacter cloacae, Pasteurella spp., Klebsiella spp. and Staphylococcus aureus were identified in 35%, 17.5%, 15% and 12.5% of the examined glands, respectively. Preputial gland inflammation was identified in 29/40 (72.5%) glands and was classified as chronic interstitial adenitis in 27 cases and suppurative adenitis in the remaining two glands. No haematological changes were found in mice with infected glands. Histologically, the presence of intralesional bacteria, intraluminal necrotic material, intraluminal keratin accumulation, interstitial inflammatory cell infiltrate and granulocytes (intraluminal and/or interstitial), along with total inflammatory score and total histopathological score, were significantly increased in infected glands and correlated with the bacterial load. Most severe inflammatory changes were identified after S. aureus infection, while ductal hyperkeratosis was significantly increased in glands infected with Klebsiella spp. In conclusion, preputial gland infection was a common event in one-year-old C57BL/6NCrl mice, and bacterial load correlated with pathological findings, while systemic effects were not highlighted by haematology.